Seismic Behavior of Concrete-Filled Steel Tube (CFST) Column and Reinforced Concrete (RC) Beam Connections under Reversed Cyclic Loading - Ahmed Najm Abdullah; Bambang Budiono; Herlien Dwiarti Setio; Erwin Lim (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Previous studies on the connection between concrete-filled steel tube (CFST) columns and reinforced concrete (RC) beams have shown a loss of joint confinement because the steel tube was completely or partially cut in the joint area. This research presents a new connection system that provides joint confinement through a continuous steel tube. Potential sliding shear at the smooth interface between the columns and beams in the joint face is mitigated using two mechanisms: (i) shear connectors and (ii) longitudinal web beam reinforcement. This study tested two CFST column and RC beam joints to 4.5% drift ratio under combined compression axial load and lateral cyclic load. The experimental results revealed no cracks at the joint zone and the specimens satisfied the ACI 374.1-05 criteria, despite minor sliding at the beam-column interface. The finite element (FE) model showed good agreement with the experimental results.